IMPLICATIONS OF MINING CONCESSION ACCEPTANCE FOR RELIGIOUS ORGANIZATIONS: A CASE STUDY OF MUHAMMADIYAH - Nugroho, Shidiq Setyo Adhi; Efendi, David (Prodi Ilmu Pemerintahan, Universitas AMIKOM Yogyakarta, 2025)
This study examines the implications of mining concessions being accepted by religious community organizations, focusing on the case study of Muhamadiyah in Indonesia. As the largest Islamic organization in Indonesia, the institution is involved in natural resource management through the acceptance of mining concessions granted by the government. This creates a dilemma between economic interests and religious, ecological and social values. The objective of this research is to analyze the impact and implications on the patron-client relationship between the government and Muhammadiyah, the relationship with local communities, and the environmental and economic implications. The methodological approach adopted is of a qualitative nature, employing a case study strategy that encompasses secondary data analysis from research documents and Indonesian mining regulations. The results indicate an ethical dilemma concerning the exploitation of resources, which is in conflict with the ideological values of Muhamadiyah, as well as with the principles of sustainability and Islamic values. Furthermore, the results demonstrate a conflict with local communities due to pollution and deforestation, and there is a risk of declining public trust in Muhamadiyah. The study's findings underscore the significance of integrating Islamic ethics through transparency and community participation to mitigate adverse effects and bolster muhammadiyah's societal function.